2013
DOI: 10.1016/j.jams.2013.01.016
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of Antioxidant and Antibacterial Activities of Six Edible Plants from Iran

Abstract: The antioxidant and antibacterial activities of six edible plants were evaluated. The active constituents of the edible plants were extracted using boiling water or 80% methanol. Results demonstrated that extraction of antioxidants by boiling water was more efficient. Lycium depressum and Berula angustifolia had the highest antioxidant activities and, therefore, could be rich sources of natural antioxidants. The antibacterial activities of the extracts were tested against Staphylococcus aureus, Escherichia col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
4
6
0
Order By: Relevance
“…Comparing the results for TP and TF obtained in this study ( Table ) with previously published data revealed that their amount does not have any chemotaxonomic significance. The range of TP and TF values of four analyzed samples of O. umbellatum in this study is similar to the range of analyzed contents of phenolics and flavonoids within O. umbellatum evaluated in other studies and three other investigated species ( Ornithogalum sintenisii , Ornithogalum cuspidatum , and Ornithogalum brachystachys ), that belong to different subgenera . Additional comparison, for the same species but different plant parts (bulbs and above‐ground part), confirms that the amount of TPs and flavonoids does not have chemotaxonomic significance, but is dependent of the biological role in plant and it is environmentally caused, as seen latter.…”
Section: Resultssupporting
confidence: 88%
“…Comparing the results for TP and TF obtained in this study ( Table ) with previously published data revealed that their amount does not have any chemotaxonomic significance. The range of TP and TF values of four analyzed samples of O. umbellatum in this study is similar to the range of analyzed contents of phenolics and flavonoids within O. umbellatum evaluated in other studies and three other investigated species ( Ornithogalum sintenisii , Ornithogalum cuspidatum , and Ornithogalum brachystachys ), that belong to different subgenera . Additional comparison, for the same species but different plant parts (bulbs and above‐ground part), confirms that the amount of TPs and flavonoids does not have chemotaxonomic significance, but is dependent of the biological role in plant and it is environmentally caused, as seen latter.…”
Section: Resultssupporting
confidence: 88%
“…The levels of total phenolics determined in the study by Tabaraki et al [25] were, therefore, within the range of the TPC values determined in this study. However, these concentrations are not comparable, as other extraction solvents were used in the study by Tabaraki et al [25], and the plant material did not originate from a tissue culture. In the future, it would be useful to test several different solvents for the extraction of phenolic compounds from Berula erecta in order to determine the most effective one.…”
Section: The Influence Of Light Wavelength and Temperature On Chlorog...supporting
confidence: 88%
“…Members of the Apiaceae family are a well-known source of natural antioxidants such as phenolic acids and flavonoids [ 23 ]. The extract of Berula angustifolia (a synonym for Berula erecta [ 24 ]) collected from the wild was rich in total phenolic compounds and showed high antioxidant activity [ 25 ]. As far as we know, no study has yet been conducted to determine chlorogenic acid in Berula erecta .…”
Section: Introductionmentioning
confidence: 99%
“…The total flavonoid content of the extract was 75.169 mg QE/g dry extract using the aluminium chloride colorimetric method (Table 1). This result indicated that the methanolic extract of medlar leaves has higher total phenolic and flavonoid content in comparison to extracts from this and other plants that have been reported in recent years [18,24,25]. A few studies have reported on the total phenolic and flavonoid content of medlar and the antioxidant capacity of its extracts.…”
Section: Phenolic and Flavonoid Contentmentioning
confidence: 52%